This preview shows page 1. Sign up to view the full content.
Unformatted text preview: same thing! However, there are simple relationships between them that you can determine from linearity. Since [ n ] = u [ n ] u [ n-1] , we must have h [ n ] = ] [ n y step- ] 1 [-n y step . Similarly, since - = = n k k n u ] [ ] [ , we must have - = = n k step k h n y ] [ ] [ ....
View Full Document
This note was uploaded on 07/05/2008 for the course ECSE 2410 taught by Professor Wozny during the Spring '07 term at Rensselaer Polytechnic Institute.
- Spring '07